PECULIARITIES OF FORMATION OF DEMAND AND SUPPLY ON THE MARKET OF RESOURCES - Н. В. Рощина (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2015)
In the article the study of the peculiarities of formation of demand and supply on the market of resources. It is proved that resources are converted into factors of production only when they are used by the enterprise. Indicated that the specificity of the object of sale determines the characteristics of the market of resources and basic laws on it. Consideration of overall demand and supply of resources, allows you to jump to the definition of the peculiarities of the law of supply and demand it is on the resource market, where the basis of this law is the ratio of marginal cost and marginal product, and its effect depends on market conditions. In addition, it was noted that to study the peculiarities of the functioning of the market of resources can also sample each of the markets that shape the market of resources, because each market has the characteristics common market resources and individual that produce it. It is shown that under the influence of the conditions under which the formation and development of market resources in Ukraine, each of its markets inherent personality traits that distinguish and define the principles of its functioning, depending on the prevailing conditions.